(untitled) - Alfred Cuschieri (Cambridge, Massachusetts, 1992)
The book provides an outline of the training programme, surgical techniques and the instrumentation needed for laparoscopic surgery. Illustrated in color throughout, it gives details of the benefits, indications and contra-indications of laparoscopic surgery. It includes the problems and difficulties of laparoscopic cholecystectomy; laparoscopic treatment of ductal calculi; laparoscopic cholangiography; and laparoscopic management of pancreatic cancer
Keywords: biliary tract - endoscopic surgery,gallbladder - endoscopic surgery,laparoscopic surgery